Developing a Novel Pediatric Eye Chart Assessing Visual Acuity by Minimum Separable Threshold - Yo Iwata (MDPI AG, 2024)
The purpose of this study was to develop a new pediatric acuity chart that can assess the minimum separation threshold by incorporating the minimum separation threshold into the picture. To overcome the design limitations of the Landolt ring, two designs of highly versatile minimum separable thresholds that can be easily incorporated into a picture were created: a black, filled circle (the "Circle") and a segment (the "Square"), both with the same break as in the Landolt ring. The three designs-the Landolt ring, Circle, and Square-were used to evaluate and compare the differences in the visual acuity of 21 healthy adults. No significant differences were observed between the results of the visual acuity tested with the Landolt ring, Circle, and Square (Landolt ring vs. Circle: p = 0.92, Landolt ring vs. Square: p = 0.31, Circle vs. Square: p = 0.40). The Bland-Altman analysis revealed no fixed errors between the Landolt ring and Circle and between the Landolt ring and Square (95% CI: −0.09-0.08, −0.09-0.12). Proportional errors were also not observed (p = 0.68, p = 0.41). The Landolt ring, Circle, and Square designs obtained equal results in visual acuity, thus achieving the successful development of a novel pediatric visual acuity chart using these designs.